2019
DOI: 10.1017/jfm.2019.565
|View full text |Cite
|
Sign up to set email alerts
|

Superharmonic instability of nonlinear travelling wave solutions in Hamiltonian systems

Abstract: The problem of linear instability of a nonlinear traveling wave in a canonical Hamiltonian system with translational symmetry subject to superharmonic perturbations is discussed. It is shown that exchange of stability occurs when energy is stationary as a function of wave speed. This generalizes a result proved by Saffman [3] for traveling wave solutions exhibiting a wave profile with reflectional symmetry. The present argument remains true for any noncanonical Hamiltonian system that can be cast in Darboux fo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
3
1
0
Order By: Relevance
“…For superharmonic disturbances (p = 0), it was shown that, even in the presence of a linear shear current (Ω = 0), steady waves lose stability at the critical amplitude, where the wave energy is an extremum, similarly to the Tanaka instability for irrotational waves (Ω = 0), as shown in figures 5 and 6. This agrees with the theoretical result by Sato & Yamada (2019). In addition, it was found that the critical wave steepness a c or the corresponding parameter γ c changes with Ω and, in particular, γ c of downstream propagating waves (Ω < 0) significantly decreases with increase of the magnitude |Ω| of the shear strength, as shown in figure 7.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…For superharmonic disturbances (p = 0), it was shown that, even in the presence of a linear shear current (Ω = 0), steady waves lose stability at the critical amplitude, where the wave energy is an extremum, similarly to the Tanaka instability for irrotational waves (Ω = 0), as shown in figures 5 and 6. This agrees with the theoretical result by Sato & Yamada (2019). In addition, it was found that the critical wave steepness a c or the corresponding parameter γ c changes with Ω and, in particular, γ c of downstream propagating waves (Ω < 0) significantly decreases with increase of the magnitude |Ω| of the shear strength, as shown in figure 7.…”
Section: Discussionsupporting
confidence: 90%
“…From these, we found that, with change of Ω, the critical point moves, but the above three properties (P1), (P2) and P3 a c 0.2229). These agree with the theoretical results by Sato & Yamada (2019). It should be also emphasized that, for downstream propagating waves (Ω < 0), the value of γ c significantly decreases with increase of |Ω|, and this may be related to the onset of wave breaking due to a sharp change of the slope Θ of the water surface shown in figure 2(b).…”
Section: Superharmonic Instabilitysupporting
confidence: 91%
See 1 more Smart Citation
“…Breaking waves are typically observed for H/λ < 1, as reviewed by Perlin, Choi & Tian (2013). Similar superharmonic instabilities also apply to the GCWs of interest here (MacKay & Saffman 1986;Sato & Yamada 2019). In the absence of surface tension, the classical KH instability associated with steady constant background flows can lead to spontaneous formation of curvature singularities along an inviscid two-fluid interface, consequently causing surface rolling and breaking (Moore 1979;Siegel 1995;Cowley, Baker & Tanveer 1999;DeVoria & Mohseni 2018).…”
Section: Nonlinear Dynamics and Simulation: Unsteady Vortex Methodssupporting
confidence: 65%